(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
In light of the corona pandemic, educational institutions have moved to learning and teaching via the Internet and e-learning ,and this is considered a turning point in course of higher education in Iraq in particular and education in general, which generated a great challenge for educational institutions to achieve the highest possible levels in practices and processes to reach the highest quality of their outputs from graduate students to the labor market that auditing performance by adopting e-learning standards is one of the effective tools that help the management of educational institutions by providing information on the extent to which they have achieved their goals through the efficient, effective and economical exploitation of available resources. The statement of the role of e-learning standards in auditing client capital is achieved by adopting a proposed performance audit program for client capital of Iraqi educational institutions by identifying e-learning standards issued by the Iraqi Ministry of Higher Education and Scientific Research and Providing performance indicators for the for Girls /University of Baghdad )in the light of the application of e-learning standards, where the research problem was identified by the absence of a special program to audit the performance of customer capital(students)according to e-learning standards, that the application of the program to audit the performance of customer capital on the research sample leads to improving the quality of the performance of the college research sample in particular and the performance of Iraqi universities in general